Grading Anterior Urethra Stricture to Predict Surgical Complexity and Outcome Using the Urethra Stricture Score - Naseem Akhtar; Ayesha Khan; Usama Bin Shaheen; Nazish Mughal; Harris Hassan Qureshi; Manzoor Hussain; Pardeep Kumar (Pakistan Journal of Health Sciences, 2026)
Urethral stricture is a cause of impedance of urine outflow and is quite common in urology. 300 out of 100,000 men are affected by this disease. There is no objective system for determining the structure's complexity. Objectives: To appraise the relationship between Urethral Stricture Score (USS) and surgical complexity, standardize the surgical approaches, and predict the surgical outcomes with the use of USS. Methods: This was a descriptive study conducted in the Department of Urology, Sindh Institute of Urology and Transplantation, Karachi. The duration for sample collection was six months. Non-probability consecutive sampling was employed. Mean and standard deviation were computed for age, duration of disease, duration of surgery, BMI, and USS. Effect modifiers like age, duration of disease, and BMI were stratified to see the effect of this on the outcome. Post stratification spearman correlation and Anova test were applied. The p-value